Produção e aplicação de embalagens ativas de TPS/PBAT por extrusão reativa contendo extrato da água do cozimento do pinhão - Silva, Tamires Barlati Vieira da (2019)
“Pinhão”, the seeds of Araucaria angustifolia (Bertol.) Kuntze, is an interesting source of natural antioxidants consumed more frequently in Brazil’s southern region. The water that results after pinhão seeds cooking, usually discharged, presents compounds with antioxidant activity, being an interesting residue that can be applied to active food packaging materials. Thus, the objective from this work was to produce active packaging formulations composed by thermoplastic starch (TPS) and poly(butylene adipate-co-terephthalate) (PBAT) added with pinhão extract, by reactive extrusion (citric acid as compatibilizer) followed by blow-extrusion. For that, the extract from pinhão cooked water was obtained through same way as cooking it for consume, followed by freeze drying. The extract had its phenolic profile determined by High Performance Liquid Chromatography (HPLC-DAD-ESI/MSn). Eight compounds were identified, the main one being catechin. Three packaging formulations were produced with addition of 0.5% (P5), and of 0.75% of extract (P75) based on the total amount of polymer, as well as a control formulation (without extract addition, CF). The films were analyzed in relation to their antioxidant activity (DPPH) indicating feasibility of applying them as active packaging. Also, were characterized the thermal properties (DSC and TGA), microstructure (SEM), mechanical properties (Texturometer), solubility, moisture content and water vapor permeation (gravimetric), contact angle with water (polar solvent) and diiodomethane (non polar), opacity (UV-Vis Spectroscopy), and color (colorimeter). The results demonstrated that the addition of the extract did not influence significantly the mechanical properties, except by P75 sample which presented significant difference (p < 0.05) from the others in relation to elongation at break. Thermal characterization it is important to note that TGA results indicate that both the films and the added extract are thermally stable up to temperatures around 250 °C, indicating that the phenolic compounds present in the extract do not degrade during the extrusion process. These results indicate that phenolic compounds are interacting with the polymer matrix. Analyzing films hydrophilicity, it was observed that films with the extract addition were less soluble in water than control formulation, the contact angle with water increased. Finally, the results indicated that the oil extracted from the nuts packaged with the active packages had lower acidity values in oleic acid (stored at 30ºC), as well as the values os specific extinction coefficients results, K232, K270 and ΔK. Thus, it can be concluded that the packaging containing pinhão extract acted in order to retard lipid oxidation of the oil present in the packed Brazilian nuts.